Areas of socio-demographic hazards in the Lubelskie Voivodeship, at the turn of the XX and XXI century. - Gałka, Jadwiga (Bulletin of Geography. Socio-economic Series, 2007)
The aim of the article was to point out reasons for the existence and spatial location of areas of socio-demographic hazards within the voivodeship, compared with the situation in the whole country, during the period of structural transformation. In order to achieve this objective, we have used the method of the demographic regress chain. The current level and deployment of the examined phenomenon both in Poland, and in the Lubelskie voivodeship, have been deeply influenced by particular demographic processes, which have taken place after the II World War, among others, the settlement of the western and northern lands, the level of internal migrations, dynamics of the natural movement, urbanization processes and various disparities regarding the national economic development. As far as the Lubelskie voivodeship is concerned, the areas which were mostly endangered with depopulation were the regions of limited communication accessibility, bad natural conditions, low level of economic development, or even real longstanding diminution of population, and major deformations within demographic structures. However, the low level of hazards was observed in the cities of the region, which was associated with the good demographic situation of these units.